Effect of edible coatings on quality of blueberry fruits under supermarket storage conditions - TOTAD, MONIKA G; SHARMA, R R; SETHI, SHRUTI; VERMA, M K (The Indian Journal of Agricultural Sciences, 2020)
Blueberry is a nutrient-rich fruit having very high antioxidant activity due to anthocyanin and phenolic compounds. However, its shelf-life is 7-8 days at ambient conditions. Thus, there is an urgent need for extending its shelf-life and availability. In order to increase blueberries shelf-life the most economic and environment friendly technique such as edible coatings stand first. In the present experiment, four edible coatings were used to evaluate their effects on shelf-life and nutrient status of blueberries. Edible coatings such as carboxymethylcellulose (CMC 1%), xanthan gum (0.3%), guar gum (0.75%) and gum Arabic (10%) were coated on the Misty blueberry fruits and then packed in punnet boxes and stored at supermarket condition (18°C and 85-90% RH). During storage, different physical and quality parameters were observed up to 18 days. Our results revealed that, all the coatings were effective in extending storage-life of coated blueberry fruits. Among the coatings, the CMC-coated Misty blueberry fruits exhibited highest score for fruit firmness (2.53 N), total soluble solids (17.52°B) and sensory evaluation score (7.79), and exhibited lowest fruit decay (1.06 %) and lipoxygenase (LOX) activity (3.34 μmoles/min/g FW). Therefore, it can be concluded that CMC (1%) was the most effective coating as it increased the shelf life of Misty blueberry from 9 days (noncoated fruits) to 18 days.